Mengelola Konflik di Lembaga Pendidikan Islam - Farid Setiawan (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2018)
AbstractThe discussion of conflict in Islamic education institution often become a polemic because there is pros and cons party. The polemic appears because of the effects given by the conflict which is caused destructive and constructive even productive. The study is done to give the understanding to a human resources in Islamic education institution that the effect of conflict doesn’t always negative, but also positive, as long as it is well managed. The descriptive-analytical method with daily cases is used in the study. The result of the study is expected become a guide for human resources and also the leaders to understand, diagnose, evaluate and solve the conflict in Islamic education institution. Human resources and the leaders can solve the problem if they have skill in understanding the situation and manage the conflict well. Skill to manage the conflict also can help the human resources become an apathetic or antipathy about the dispute and quarreling. It is because conflict is a part of the process to make dynamic the atmosphere of the Islamic education institution so that it will not always be a focus on routine activities, technical, and administrative.Keyword: Conflict Management, and Islamic Education Institution.AbstrakPerbincangan seputar konflik di lembaga pendidikan Islam seringkali dihadapkan dengan polemik, ada yang mendukung dan menolak. Polemik ini muncul karena dampak ganda konflik yang bisa destruktif dan konstruktif, bahkan produktif. Studi ini dilakukan untuk memberi pemahaman kepada Sumber Daya Insani (SDI) di lembaga pendidikan Islam bahwa konflik tidak selamanya berdampak negatif, tetapi bisa juga positif, selama dikelola dengan baik. Dengan metode deskriptif-analitis dan disandingkan kasus-kasus sehari-hari, studi ini diharapkan bisa menjadi panduan bagi SDI maupun pimpinan untuk memahami, mendiagnosa, menilai dan menyelesaikan konflik di lembaga pendidikan Islam. SDI atau pimpinan akan dapat melakukan hal-hal itu jika memiliki keterampilan dalam memahami situasi dan mengelola konflik yang baik. Dengan keterampilan itu maka SDI di lembaga pendidikan Islam diharapkan tidak lagi apatis atau antipati terhadap setiap perselisihan dan percekcokan. Sebab konflik merupakan bagian dari proses untuk mendinamisasikan iklim lembaga pendidikan Islam agar tidak selalu terjebak pada kerja-kerja rutinan, teknis dan administratif. Kata Kunci: Mengelola Konflik, and Lembaga Pendidikan Islam.